Potential, spatial distribution and sustainability of sugarcane-ethanol in Brazil: projections to 2030 - Souza, Karina Rogério de Oliveira Viana (2017)
The sugarcane-ethanol sector is very important for the Brazilian economy, as it contributes to the country’s GDP and generates a great number of jobs. In addition, it contributes to Greenhouse gas (GHG) mitigation by replacing fossil fuels. However, as this sector depends on a long term economic policy and is reason for socio-economic and environmental concerns, it has a future full of uncertainties. Therefore, the aim of this study is to identify, measure and assess these doubts to estimate ethanol demand and to assess the sustainable potential of sugarcane, of the current and future (2030) production, taking into account technical, economic and sustainability constraints. From a comparison of different projection models, the potential ethanol demand range for 2030 is defined. It is estimated that Brazil will demand 61.7 GL of EtOH in 2030, in the optimistic scenario, and 49 GL EtOH in the pessimistic scenario. Once demand is determined, the potentials of sugar cane ethanol production are calculated. A resource-focused assessment with a spatially explicit analysis is realized, using the geographic information system ArcGIS. The results for 2012 and 2030 scenarios, show that theoretically Brazil has a vast potential for sugarcane production, but when technical-economic constraints are taken into consideration, it significantly decreases. The same is true for the environmental and sustainable potential. Environmental criteria regarding the GHG emission reduction of and the protection of biomes are those that have the greatest impact on the reduction of the productive potential. For 2012 the highest sustainable potential for sugarcane is 0.76 EJ EtOH, but this can increase to 1.61 EJ EtOH towards 2030 if improvements happen in the fields and in industry. The results are lower than expected, but still represents sufficient production to meet the domestic demand. Concerning the increase in international market share, the results are not positive and suggest that Brazil will hardly have surplus in sustainable production for export, following assumptions made in this study.